Study the Personality of Arjuna Award-Winning Paralympian Bhavina Patel - Vasava Krunalkumar Madhubhai; Dr. Vipul H. Upadhyay (International Journal of Scientific Research in Humanities and Social Sciences, 2025)
This research study was conducted on the person of Arjuna Award winning Paralympian Bhavina Patel in the field of sports. For the purpose of this study, the persons related to the subject, persons associated with sports as well as persons who are their personal friends, neighbors and family members were selected to collect all the necessary information related to the research. In this research study, a self-designed questionnaire was used for the person study. After administering the questionnaires and verifying the information determined through interviews, the responses of the attitudes in each questionnaire were averaged and analyzed. The conclusions were as follows. 1. She has a very sociable nature. 2. She is a very friendly and helpful person. 3. She is very conscious about his health. 4. She does not have a stubborn nature. 5. She never loses control over his anger. Most people were found to completely agree with the opinions of all five of these statements.